Impact of transaction-oriented financial assets on firm innovation in China: effects of liquid reserve and risk mitigation - Wenjing Yu; Qilin Zhan; Waqar Ameer; Xiaohui Zeng (Humanities & Social Sciences Communications)
Abstract This study examines the impact of transaction-oriented financial assets on firm innovation using data from non-financial listed firms in China’s A-share market from 2008–2019. These findings suggest that transaction-oriented financial assets promote innovation. Specifically, such an allocation mitigates the influence of external financing constraints on firms by providing continuous financial support for innovation activities, thereby demonstrating the liquidity reserve effect of transaction-oriented financial assets. Furthermore, combining transaction-oriented financial assets with innovation investments facilitates risk diversification, enabling firms to engage in high-risk innovative activities at manageable risk levels. This reflects the portfolio effects of transaction-oriented financial assets. Governments should actively enforce financial sector reforms to address the financing challenges associated with firm innovation. Additionally, improving the risk-warning system and innovation risk compensation mechanism can more substantially support non-financial firms’ innovation activities.